Analisis Optimasi Digital Marketing Dalam Meningkatkan Jumlah Konsumen Tour dan Travel di Masa Pandemi (Studi Kasus Pada PT Hijrah Madani Istiqomah Tour) - Chayati , Cory; Upe, Rachman; Thaha, Abbas (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2024)
The travel business, both for business travel, tourism, general, Hajj and Umrah is currently one of the sectors that has the most impact caused by the Covid-19 pandemic. With the policy of closing access in and out of the region both by air and land and sea, the travel business has received a big blow. One of them is PT Hijrah Madani Istiqomah Tour which must implement its marketing strategy and optimize its digital marketing in increasing the number of consumers. This research aims to 1). Analyzing the marketing strategy implemented by PT Hijrah Madani Istiqomah Tour in increasing the number of consumers 2). Analyzing the optimization of digital marketing carried out by PT Hijrah Madani Istiqomah Tour in increasing the number of consumers 3). Understand and analyze the supporting and inhibiting factors of the digital marketing process in increasing the number of consumers of PT Hijrah Madani Istiqomah Tour. This study uses a qualitative approach with the type of field research. The data collection technique uses observation, interviews and documentation. The data analysis used is descriptive. The results of this study show that: 1) The implementation of marketing strategies through the process and stages of STP (Segmentation, Targeting and Positioning), where the strategy applied is adaptive strategy. 2) Optimization of digital marketing in increasing the number of prospective consumers of Hajj and Umrah pilgrims through planned and well-organized digital media management, and being able to be consistent in uploading content and being able to serve consemun in a friendly manner. 3) The inhibiting and supporting factors in increasing the number of consumers are as follows. a) The supporting factors, easy access to social media, and minimal promotional costs in the media. b) The inhibiting factors, the lack of human resources and the control are relatively weak.